"A prospective study of assessment of neurocognitive function in illiterate patients with gliomas treated with chemoradiation": Assessment of neurocognitive function in gliomas. (2021) - Valiyaveettil, Deepthi; G, Ashalatha; Malik, Monica; Eaga, Prathyusha; Ahmed, Syed Fayaz; Joseph, Deepa
Highlights: Neurocognitive dysfunction in gliomas is multifactorial. Neurocognitive assessment is an essential component in glioma patients. We assessed using the ACE III questionnaire prior to radiation and on follow up. Higher dose to stem cell compartments showed decline in some domains of assessment. Abstract: Objective: Neurocognitive functioning (NCF) is an important component of quality of life (QoL) in glioma patients. The neurocognitive toxicity from irradiation of brain tumours may be related to damage to neural progenitor cells (NPC). The aim of our study was to assess the NCF in illiterate glioma patients. Methods: This was a prospective study done in glioma patients admitted for adjuvant treatment. Illiterate and semiliterate post op glioma patients with ECOG PS ≤ 3 were included. Neurocognitive assessment was done using Addenbrooke's Cognitive Examination (ACE-III) questionnaire prior to the start of RT and at 6month and 12 month follow up. The scores were correlated to the doses to sub ventricular zone (SVZ) and sub granular zone (SGZ) regions. Results: 20 patients were recruited.16 patients were illiterate and four patients were semiliterate. Median of the mean dose to the SVZ I/L (ipsilateral) was 48.5 Gy and SGZ I/L was 39.5 Gy. In patients who received ≤49 Gy mean dose to SVZ I/L, there was statistically significant improvement in memory, fluency, language and total ACE scores at six months. In patients with SGZ I/L mean dose ≤40 Gy, there was improvement in memory, language, and total ACE score at six months. Similar trend continued at 12 months follow up. Conclusions: NCF assessment by ACE III questionnaire is a useful tool even in illiterate patients. Lower RT doses to the ipsilateral SVZ and SGZ showed significant improvement in total ACE scores at 6 months and improvement in specific domains at 6 and 12 months.